1975
DOI: 10.1002/jcp.1040850105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of glycolipids and phospholipids in hamster cells: Dependence on cell density and the cell cycle

Abstract: Sakiyama et al. ('72) reported the isolation of a line of hamster cells (NIL l c l ) which contains only three glycolipids, hematoside, ceramide monohexoside and ceramide dihexoside. The incorporation of radiolabeled palmitate into hematoside during 24 hours was three fold higher in normal confluent, non growing cells than sparse, growing ones, Polyoma transformed cells did not exhibit this effect.We have continued studies with the untransformed cell line and have found that the higher incorporation of radiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
1979
1979

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Only 20% of these cells had reattached to the plate 4 h after removal of the buffer and resuspension in growth medium; in contrast, cells that had been trypsinized, centrifuged, and resuspended in growth medium without a 1-h incubation with buffer, showed 80% attachment at the same time. After 24 h, these cells had tripled in number (consistent with a doubling time of approximately 16 h (Hirschberg et al, 1975) , while the EDTA-treated cells had increased by only 20%. Numerous cell fragments could be observed under microscopic examination of these preparations.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Only 20% of these cells had reattached to the plate 4 h after removal of the buffer and resuspension in growth medium; in contrast, cells that had been trypsinized, centrifuged, and resuspended in growth medium without a 1-h incubation with buffer, showed 80% attachment at the same time. After 24 h, these cells had tripled in number (consistent with a doubling time of approximately 16 h (Hirschberg et al, 1975) , while the EDTA-treated cells had increased by only 20%. Numerous cell fragments could be observed under microscopic examination of these preparations.…”
Section: Resultsmentioning
confidence: 63%
“…Previous studies have shown that in the lcl clone of NIL cells (a line of hamster fibroblasts) the sialic acid containing glycolipid "hematoside", the principal glycolipid of this cell line, increases twoto threefold in amount when sparse cells become confluent (Sakiyama et al, 1972;Hirschberg et al, 1975). Since such an increase could be related to the presence of 7 From the Department of Biochemistry, St. Louis University School of Medicine, St. Louis, Missouri 63104.…”
mentioning
confidence: 99%
“…However, for such a mechanism to take place one would have to postulate a very low concentration of the intermediate radiolabeled N-acetylmannosamine. An unequivocal answer to this problem can be obtained by using a mixture of [1-I4C] -and [4,5,6,7,8,9-3H] -N-acetyl neuraminic acid as precursor; such Although analyses of the PTA-soluble material have shown radiolabeled sialic acid…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot was applied to a thin layer plate and developed in chloroform-methanol-water, 60:35:8, as previously described (6). Standard hematoside was obtained by growing cells with l-['4C]-palmitate (7).…”
Section: Lipid Extractionmentioning
confidence: 99%